Comparison of muscle physiology and performance outcomes from either relative intensity or repetition maximum training - Carroll, K. (2018)
The main purpose of this dissertation was to compare performance and physiological outcomes of between a repetition maximum (RM) and a relative intensity using sets-and-repetitions (RISR) resistance training (RT) program in well-trained lifters. Fifteen subjects underwent RT 3 d·wk-1 for 10-weeks in either a RM group (n=8) or RISR group (n=7). The RM group achieved a relative maximum each day while the RISR group trained based on percentages. Testing included percutaneous needle biopsies of the vastus lateralis, ultrasonography, unweighted (g to assess within and between-group alterations. RISR from pre-to-post yielded statistically significant increases in Type I CSA (p=0.018), Type II CSA (p=0.012), ACSA (p=0.002), unweighted (p=0.009) and 20 kg SJ JH (p=0.012), unweighted (p=0.003) and 20kg SJ PPa (p=0.026), IPF (ppSR increased in unweighted (p=0.023) and 20kg SJ JH (p=0.014), and 20kg SJ PPa (p=0.026) from pre-to-post taper. RM yielded statistically significant increases from only pre-to-post taper for 20kg SJ JH (p=0.003) and CMJ JH (p=0.031). Additionally, RM had a statistically significant pre-to-post decrease in RFD from 0-50ms (p=0.018) and 0-100ms (p=0.014). Between-group effect sizes supported RISR for Type I CSA (g=0.48), Type II CSA (g=0.50), ACSA (g=1.03), all MYH isoforms (g=0.31-0.87), all SJ variables (g=0.64-1.07), unweighted and 20kg CMJ JH (g=0.76-0.97), unweighted CMJ PPa (g=0.35), IPFa (g=0.20), and all RFD (g=0.31-1.25) time-points except 0-200ms; with all other effects being of trivial magnitude (gSR training yielded greater improvements in vertical jump, RFD and maximal strength compared RM training. These performances results may, in part, be explained mechanistically by the superior physiological adaptations observed in the RISR group within the skeletal muscle. Taken together, these data support the use of RISR training in well-trained populations.